If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11(x) + -6 = -336 Reorder the terms: -6 + 11x = -336 Solving -6 + 11x = -336 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 11x = -336 + 6 Combine like terms: -6 + 6 = 0 0 + 11x = -336 + 6 11x = -336 + 6 Combine like terms: -336 + 6 = -330 11x = -330 Divide each side by '11'. x = -30 Simplifying x = -30
| 3[9(x+4)+2(x+1)]=0 | | 7(m-81)=84 | | 5(g-73)=95 | | 2(y+2)(x-3)(1-y)=0 | | 0.9-0.5y=4.4 | | x(b-3)=0 | | (11b-6)-5(2b+1)=2 | | 4x(x-1)-7x(x-6)=5x(x+6) | | (5u-6)(4-u)=0 | | 5(3+n)+2n=-27 | | D=1/8(h)(a-b) | | E^y^1/6/y^1/2 | | 5(d+9)=5(d-7) | | 14=4j-2 | | 3x7/27x2y | | 0.16x+0.5(x-5)=0.01(5x-2) | | 4+11=15 | | 2a+3b=cfora | | -2(6-x)+8=6-4(x+2) | | 7(10)-3w=5(15-4w) | | x(3x-2)+x(4x-2)=(7x+8)(x-4) | | -7+5m+6=-27 | | 3(2x+7)=7-2(x-7) | | 3-10(x)=127 | | 2r+2=-3r-5+5 | | 4/3*3.14*5^3 | | n+14=6 | | -5k-3=-33 | | f(x)=3x-1/x^3 | | 3x-7x+8=2/3 | | y=140/x | | (x-8)(x-8)-1=0 |